2022
DOI: 10.3390/audiolres12020015
|View full text |Cite
|
Sign up to set email alerts
|

Is Skull Vibration-Induced Nystagmus Useful in Vestibular Neuritis Follow Up?

Abstract: The aim of this study was to evaluate the vestibulo-ocular reflex (VOR) gain and the saccade regrouping pattern PR score of the Video Head Impulse Test (vHIT) and its relationship with the slow-phase velocity (SPV) of skull vibration-induced nystagmus (SVIN) in recovery after a unilateral vestibular loss (UVL). A total of 36 patients suffering from vestibular neuritis (VN) were recruited and followed up for twelve months. In every visit, horizontal vHIT and an SVIN were performed, as well as VOR gain; PR score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…We have seen reduction of the intensity of nystagmus in all the patients of our study being the most frequent finding the incomplete. As previous authors have shown the intensity of SVIN (as measured by the aSVINwo) correlates to the degree of asymmetry in the VOR between the right and left vestibules [4,12]. In patients with UVL, we have also shown that the amount of reduction of SVIN as measured with the FISVIN correlates to both: the asymmetry of gain of the VOR and the intensity of SVIN.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We have seen reduction of the intensity of nystagmus in all the patients of our study being the most frequent finding the incomplete. As previous authors have shown the intensity of SVIN (as measured by the aSVINwo) correlates to the degree of asymmetry in the VOR between the right and left vestibules [4,12]. In patients with UVL, we have also shown that the amount of reduction of SVIN as measured with the FISVIN correlates to both: the asymmetry of gain of the VOR and the intensity of SVIN.…”
Section: Discussionsupporting
confidence: 76%
“…To test for vestibular function, the video head impulse test (vHIT) provides fast and accurate information. It has been shown that SVIN intensity correlates with the amount of vestibular deficit obtained in the vHIT [12,13]. A similar correlation was also found before when the relative asymmetry between the right and left inner ear function was evaluated with the caloric test [14].…”
supporting
confidence: 78%
“…All patients showed a reduction in the intensity of nystagmus, with incomplete fixation the most frequent finding. It has previously been reported that the intensity of SVIN (as measured by the aSVINwo) correlates to the degree of asymmetry in the VOR between the right and left vestibules [ 4 , 14 ]. In patients with UVL, the amount of reduction in SVIN as measured with the FI SVIN correlates to both the asymmetry of gain of the VOR and the intensity of SVIN.…”
Section: Discussionmentioning
confidence: 99%
“…A video head impulse test (vHIT) provides fast and accurate information on the functional status of the semicircular canal afferents in the high-frequency domain. Although it is considered that vHIT examines high-frequency sensible hair cells, while SVIN, as well as the caloric test, examine the low-frequency sensible vestibular hair cells [ 13 ], it has been shown that SVIN intensity correlates with the amount of vestibular deficit obtained in the vHIT [ 14 , 15 ]. A similar correlation has also been found in case of functional asymmetry between the two horizonal semicircular canals at the caloric test [ 16 ].…”
Section: Introductionmentioning
confidence: 99%